Upaya Peningkatan Status Bandara Frans Kaisiepo Biak Sebagai Bandara Internasional - Muslim Lobubun (Kyadiren, 2019)
This study aims to identify the existence of Biak’s Frans Kaisepo Airport as an international airport. This research was conducted in Biak Numfor Regency. The data was collected through the interview method and then analyzed through descriptive and qualitative analysis. This study shows that the existence of a Regional Regulation (Perda) regulates the existence of the Airport. In the era of Papua's special autonomy, there is a possibility that there will be government compensation for the rights of indigenous peoples and there is no agreement between several clans who consider the customary land owners where the Airport was established, including the lack of public awareness in maintaining and protecting the Airport as a regional asset in increasing Regional Original Income (PAD), as well as efforts to improve community welfare based on the mandate of Law Number 1 of 2001 (Special Autonomy for Papua Province) and Law Number 1 of 2009 concerning Aviation.